LECTURERS’ READINESS FOR INTEGRATING ARTIFICIAL INTELLIGENCE (AI) IN TEACHING, LEARNING, AND RESEARCH ACTIVITIES IN EDUCATIONAL INSTITUTIONS (NAU Journal of Technology and Vocational Education, 2025)
The study determined lecturers’ readiness for integrating Artificial Intelligence (AI) in teaching, learning, and research activities in educational institutions. Three research questions and three hypotheses were answered and tested in this study. A descriptive research design of survey type was used. The population of this study comprised 921 academic staff of Olabisi Onabanjo University (OOU) and Tai Solarin University of Education (TASUED).  A total of 150 academic staff of Olabisi Onabanjo University (OOU) and Tai Solarin University of Education (TASUED) were selected as sample size of the study, using purposive sampling technique. A self-researcher-designed instrument tagged: Lecturers’ Readiness, Integrating Artificial Intelligence, Teaching, Learning, and Research Activities Questionnaire (LRIAITLRAQ) was used for data collection with 0.83 as reliability coefficient. Descriptive statistics of mean and standard deviation were used for answering research questions. Hypotheses were tested using PPMC. The findings of the study revealed that there was low level of lecturers’ readiness for integrating Artificial Intelligence (AI) in teaching within higher educational institutions. There was low level of lecturers’ readiness for integrating Artificial Intelligence (AI) in learning within higher educational institutions. There was medium level of lecturers’ readiness for integrating Artificial Intelligence (AI) in research activities within higher educational institutions. Integration of Artificial Intelligence (AI) do enhance teaching (B = 0.426, t = 8.772, p < .05), learning (B = 0.502, t = 14.201, p < .05) and research activities (B = 0.787, t = 31.175, p < .05) in higher educational institutions in higher educational institutions. It was recommended that universities management should integrate AI components into the curriculum. Additionally, lecturers are encouraged to use AI to enhance personalized teaching-learning experiences, and effectively manage course content, assessments, and student communication.
Keywords: Lecturers’ Readiness; Artificial Intelligence Teaching; Learning; Research Activities Educational Institutions